Phenolic Extracts from Vaccinium corymbosum L. Loaded in Microemulsions and Liposomes as Enhancers of Olive Oil Oxidative Stability - Nikolina Liović; Perica Bošković; Ivana Drvenica; Anet Režek Jambrak; Ana Marija Dropulić; Greta Krešić; Viktor Nedović; Branko Bugarski; Zoran Zorić; Sandra Pedisić; Tea Bilušić (Polish Journal of Food and Nutrition Sciences)
Natural phenolic compounds are recognized as bioactive ingredients in food but can also have a role as effective alternatives to synthetic antioxidants in stability improvement of foods prone to oxidation, such as edible oils. This study aimed at the preparation and HPLC-DAD characterization of phenolic extracts from Vaccinium corymbosum L. (raw, pasteurized, freeze-dried and treated with high-intensity ultrasound), and at testing their antioxidant potential in the prevention of olive oil oxidation in the native state and encapsulated into microemulsions and liposomes systems. Water-in-oil structured microemulsions used in this study were prepared using mechanical, ultrasonic, and high pressure homogenization. Liposomes with the average size of 589.1±2.9 nm were produced with the proliposome method using commercially available phosphatidylcholine – Phospolipon 90G. The obtained results showed significant prolongation of the oxidative stability of extra virgin olive oil enriched with encapsulated blueberry phenolic extracts than with native phenolic extracts, regardless of the method used for blueberry processing. Phenolic extracts encapsulated in microemulsions had a stronger effect on the prolongation of olive oil oxidative stability in comparison with the extracts encapsulated in liposomes. The average prolongation rate of oxidative stability was 45.65% by phenolic extracts encapsulated in microemulsions prepared by mechanical homogenization (p=0.012), and 58.72% by microemulsions prepared by ultrasound homogenization (p=0.011). Phenolic extracts encapsulated in microemulsions prepared by high pressure homogenization had no effect on oil oxidative stability prolongation.